Investigating the influence of aesthetic preferences on packaging product design - Ding, Sinong; Yahaya, Mohd Faiz; Abdul Rahman, Ahmad Rizal (Common Ground Research Networks, 2024)
Aesthetics is crucial to product design and influences consumer product choices. The purpose of this study is to investigate the effect of aesthetic preferences on packaging products and provide a preliminary literature review and analysis of aesthetics and background knowledge on packaging products. A literature search of the online catalog was conducted using the search terms “aesthetic preference,” “aesthetic pleasure,” “visual aesthetic,” “product design,” and “packaging.” Through preliminary screening and full-text screening, sixty-one relevant articles were finally selected. The aim is to explore the importance of aesthetics in influencing consumers’ aesthetic preferences and perceptions of packaging products and the main factors influencing aesthetic responses and packaging design. According to the multidimensional nature of aesthetics, research based on the Unified Model of Aesthetics may more systematically investigate the impact of aesthetic preferences on packaging products and fill the gap in the field. We found that emphasizing visual aesthetics, paying attention to aesthetic principles, and aesthetic multidimensionality may help arouse consumers’ desire to purchase and bring a better user experience to consumers. Finally, understanding aesthetic preferences may provide researchers and designers with guidance and design steps related to the product aesthetics literature.